1996
DOI: 10.1103/physreve.53.5637
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of a fracture surface by atomic force microscopy

Abstract: The fracture surface of a Ti 3 Al-based alloy is studied using both an atomic force microscope and a standard scanning electron microscope. Results are shown to be quantitatively comparable. Two fracture regimes are observed. It is shown in particular that the roughness index characterizing the small lengthscales regime is equal to 0.5. Furthermore, the large lengthscales fractal domain is found to spread over nearly six decades of lengthscales.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
47
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 33 publications
9
47
0
Order By: Relevance
“…≈ 0.55) was observed on metallic fracture surfaces [8][9][10] at small length scales/low crack velocities. It was shown that the crossover length separating this regime from the ζ 0.75 regime at higher length scales was inversely proportional to the average crack velocity V .…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…≈ 0.55) was observed on metallic fracture surfaces [8][9][10] at small length scales/low crack velocities. It was shown that the crossover length separating this regime from the ζ 0.75 regime at higher length scales was inversely proportional to the average crack velocity V .…”
mentioning
confidence: 94%
“…Bonamy et al [12] have shown that the set of exponents {ζ 0.75, β 0.6} define a universality class corresponding to length scales smaller than the process zone size, where non linear elastic processes take place. Above this process zone size, another university class is observed [12,20,21] characterized by a set of exponents {ζ 0.4, β 0.5} that can be understood theoretically within the Linear Elastic Fracture Mechanics framework.A third regime arises at very small length scales, characterized by a roughness index close to ζ ≈ 0.5, observed in a metallic alloy and in a soda-lime silicate glass [8][9][10] along a direction perpendicular to the direction of crack propagation. This regime was suggested [22] to be…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The phenomenology of the crack propagation is wellestablished by recent experimental studies [3][4][5][6][7][8][9]: once a flux of energy to the crack tip passes the critical value, the crack becomes unstable, it begins to branch and emits sound. Although this rich phenomenology is consistent with the continuum theory, it fails to describe it because the way the macroscopic object breaks depends crucially on the details of cohesion on the microscopic scale [10].…”
mentioning
confidence: 99%